Altruism, Welfare, or Development Aid? Swedish Aid for Family Planning in Ceylon, 1958 to 1983. Issue 4 (1st December 2016) - Thoradeniya, Darshi
Abstract : In engaging critically with the history of the Sweden-Ceylon Family Planning Programme, the author brings in both local and global debates on population, development, the welfare state, and Swedish neutrality in Cold War politics to show that these were not necessarily one-way processes but reciprocal processes. The methodology included the analysis of secondary sources, archival records, and contemporary debates that were published in Sri Lankan newspapers. It is clear that global debates did not simply transfer to Third World countries; this encounter (global and local) allowed space for negotiations and translations of global and local politics of development. These were reciprocal processes in many ways. On the one hand, for example, a social engineering project cemented the population and national development plans of postindependence Sri Lanka, while on the other hand Sweden was acting strategically so as to maintain its neutrality in Cold War politics.